Pengaruh Kekuatan Pembuktian Kesaksian yang Berdiri Sendiri Terhadap Putusan Perkara Pidana - Dimas Farhann Danu Pratama (HUMANIORUM, 2023)
According to data from the Central Statistical Agency (2021), although Indonesia's crime rate has declined marginally over the past five years, this figure does not accurately reflect the strength of the country's legal system. There are at least 247,218 cases in 2020 and 239,481 cases in 2021. The existence of a judge's ruling is a crucial component of concluding a criminal case. Although witness testimony can be used as evidence in court, one sort of witness statement, known as "stand-alone testimony," is currently being researched for its potential. With respect to the case's comprehension, the author of this study will explore the problem's subject utilizing a legal-justice research methodology (Soekanto, 1986). This study was also carried out using the approach of statutory regulations and applicable theories. Based on the results and discussion above, the authors draw the conclusion that there is an effect of the strength of evidence from independent testimony on criminal case decisions, but it is not significant. The judge cannot use testimony that stands alone as evidence because the testimony is counted as a single testimony, which does not meet the standard as a consideration in deciding a crime against the defendant.